Adoption Levels of Cocoa Rehabilitation Programmes in South West Nigeria - Oluwole Matthew Akinnagbe (Indonesian Coffee and Cocoa Research Institute, 2020)
Cocoa is an important crop to the economies of countries such as Nigeria, Cote D’Ivoire, Ghana and Cameroon in West Africa. This study ascertained the adoption levels of farmers in cocoa rehabilitation programmes in South West, Nigeria. Data for the study were collected from 240 cocoa farmers through the use of interview schedule and focus group discussion. Multistage sampling procedure was used in selecting respondents. Data were analysed using percentage and mean statistics. Results revealed that, adoption index was high in planting young cocoa seedlings under old cocoa trees for the three groups of farmers - farmers that benefitted from government agency cocoa resuscitation programme (98.0%), farmers that benefitted from non-governmental agency cocoa resuscitation programme (94.0%) and farmers that benefitted from both governmental and non-governmental agencies cocoa resuscitation programmes (95.0%). Low adoption index (38.0%, 32.0% and 33.0%) were recorded in coppicing technique for the three groups of farmers, respectively. The most helpful agency in the adoption of cocoa resuscitation programmes was Agricultural Development Programme (M=2.80). To improve the level of adoption of cocoa resuscitation programmes, Federal Government of Nigeria through Ministry of Agriculture should provide more incentives geared towards encouraging increased participation of the organized private sector in cocoa production.